2022
DOI: 10.3390/jmmp6020030
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking of 316L Stainless Steel Manufactured by a Hybrid Additive/Subtractive Technology

Abstract: This research study investigated the hybrid processing of 316L stainless steel using laser powder bed (LPB) processing with high-speed machining in the same build envelope. Benchmarking at four laser powers (160 W, 240 W, 320 W, and 380 W) was undertaken by building additively with machining passes integrated sequentially after every ten deposited layers, followed by the final finishing of select surfaces. The final geometry was inspected against the computer-aided design (CAD) model and showed deviations smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…The averaged tensile properties of the samples are summarized in Table 1 . In general, all three sample types’ mechanical properties resemble those published by EOS GmbH [ 41 ] and are consistent with further benchmark values, as summarized by Sarafan et al [ 42 ] Shear failure in textured (high Mn) TWIP steels was reported by Li et al [ 37 ] A Goss texture in those specimens was induced by a rolling process and resulted in a comparable stress–strain curve as well as shear fracture, similar to the present case.…”
Section: Resultssupporting
confidence: 91%
“…The averaged tensile properties of the samples are summarized in Table 1 . In general, all three sample types’ mechanical properties resemble those published by EOS GmbH [ 41 ] and are consistent with further benchmark values, as summarized by Sarafan et al [ 42 ] Shear failure in textured (high Mn) TWIP steels was reported by Li et al [ 37 ] A Goss texture in those specimens was induced by a rolling process and resulted in a comparable stress–strain curve as well as shear fracture, similar to the present case.…”
Section: Resultssupporting
confidence: 91%
“…In a previous study by Sarafan et al [31], it was demonstrated that the porosity of samples could be influenced by the laser power. Increasing the laser power from 160 W to 380 W resulted in a corresponding increase in density from 98.1% to 99.5%.…”
Section: Microstructural Characterization Of Undeformed Samplesmentioning
confidence: 96%
“…11 However, if the cooling rates are too fast, the -ferrite can be retained even at room temperature and can negatively affect the fracture toughness and corrosion resistance. 18,19 Therefore, a powder composition specification aimed at minimizing the -phase formation at the end of solidification would be critical to avoid the possibility of any retained -ferrite at room temperature. To determine a compositional specification for 316SS-L, 1,000 compositions were chosen, all of which were within the ASTM specifications shown in Table 1.…”
Section: Calphad and Data Mining For Compositional Specificationsmentioning
confidence: 99%